Pemikiran Ki Hajar Dewantara tentang Pendidikan yang Memerdekakan dan Implikasinya terhadap Implementasi Pendidikan di SMP - Ricky Yoseptry; Khoirunnisa Khoirunnisa; Liza Putri Renata; Fatmawati Fatmawati; Wachyudin Wachyudin (STKIP PGRI SITUBONDO, 2025)
The changes brought about by digital technology have had a significant impact on the process of identity formation among adolescents, particularly junior high school students who are in a transitional phase toward adulthood. In the environment of SMPN 2 Babakan Cikao Purwakarta, the use of social media and intense digital interaction has given rise to various issues, such as a tendency toward self-comparison, a decline in the authenticity of expression, anxiety over social judgment, and experiences of alienation from the real environment. This situation indicates the need for an educational approach that is able to address the personal dimension and the meaning of students’ lives. This study examines the relevance of existentialist thought, particularly the ideas of Sartre, Kierkegaard, and Frankl, as a foundation for guiding adolescents to understand themselves more holistically amid the flow of digitalization. The study is conducted using a descriptive qualitative research method based on a literature review, examining various relevant academic sources. The results show that adolescents face challenges such as undirected freedom, pressure to conform, the need for digital recognition, and a sense of meaninglessness. Through education grounded in existential values, teachers can act as facilitators who help students develop responsibility, moral courage, reflective thinking, healthy human relationships, and deeper ethical awareness. The findings of this study emphasize the importance of integrating an existential perspective into the learning process so that students are able to build a more mature identity and discover an authentic direction in life.